Principal component analysis of free throw shot trajectories in relation to shooting performance - Adler, W. R.; Kipp, K.; Ahn, N. (ISBS Proceedings Archive (Michigan), 2023)
The purpose of this study was to analyze free throw (FT) shot trajectories of individual basketball players using principal component analysis (PCA) and investigate whether variation in trajectories correlated with FT shooting performance. A markerless motion capture system was used to record three-dimensional FT shot trajectories of seven basketball players during practice. Horizontal and vertical positioning of the wrist joint center of the shooting hand were captured in both the sagittal and frontal planes for all trials. These coordinates were used as the input to the PCA. Positive correlations between the amount of variation accounted for by the first principal component and FT shooting performance (in-game FT%) suggest that players with simpler and less variable (i.e., more deterministic) shooting trajectories are better FT shooters.